2010
DOI: 10.1590/s0100-06832010000400006
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade máxima de adsorção de fósforo relacionada a formas de ferro e alumínio em solos subtropicais

Abstract: RESUMO(1) Recebido para publicação em setembro de 2009 e aprovado em maio de 2010.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 24 publications
(42 reference statements)
1
13
0
12
Order By: Relevance
“…The MACP values increased by 63.5 and 1,926.8 mg kg -1 for the soils SXe-Cachoeira do Sul and CHa1-São Francisco de Paula, respectively. The MACP was significantly correlated with the P-rem values (r = -0.74 ** ), as expected, because the measurement of P-rem is a point among those used in the adsorption isotherm for determination of the MACP (Vilar et al, 2010;Broggi et al, 2011); however, the correlation was not statistically significant with the clay content (r = 0.26 ns ) ( Table 3). Possibly due to the utilization of a large number of mineralogically distinct soils, the results of this work contradicts those of other studies that obtained a significant relationship between the MACP and clay (Corrêa et al, 2011;Pinto, 2012).…”
Section: Relationship Between the Physical And Chemical Properties Ofsupporting
confidence: 72%
See 1 more Smart Citation
“…The MACP values increased by 63.5 and 1,926.8 mg kg -1 for the soils SXe-Cachoeira do Sul and CHa1-São Francisco de Paula, respectively. The MACP was significantly correlated with the P-rem values (r = -0.74 ** ), as expected, because the measurement of P-rem is a point among those used in the adsorption isotherm for determination of the MACP (Vilar et al, 2010;Broggi et al, 2011); however, the correlation was not statistically significant with the clay content (r = 0.26 ns ) ( Table 3). Possibly due to the utilization of a large number of mineralogically distinct soils, the results of this work contradicts those of other studies that obtained a significant relationship between the MACP and clay (Corrêa et al, 2011;Pinto, 2012).…”
Section: Relationship Between the Physical And Chemical Properties Ofsupporting
confidence: 72%
“…The lack of correlation between the clay content and Fe OX is an indication that soil clay accumulation is not necessarily associated with the presence of Fe oxides of low crystallinity, which are described as having a high capacity of P adsorption (Hernández and Meurer, 1998;Donagemma et al, 2008). In addition to crystalline Fe oxides and clay minerals 1:1 (such as kaolinite), which have a lower potential to adsorb Fe oxides of low crystallinity, they can also significantly affect the adsorption of P, mainly due to the higher quantity generally found in soils (Torrent et al, 1994;Vilar et al, 2010). In a study with 60 RS soils, Oliveira (2015) found a significant correlation, although weak (r = -0.31 * ), between the P-rem and the area of kaolinite obtained by x ray diffraction.…”
Section: Relationship Between the Physical And Chemical Properties Ofmentioning
confidence: 99%
“…Os teores de P encontrados se encontram abaixo da capacidade máxima de adsorção para grande parte dos solos de regiões subtropicais (Vilar et al, 2010). Avalia-se, porém, que a aplicação continuada de adubos orgânicos e minerais pode resultar, nessas taxas, em problema de perdas de fósforo sob formas de sedimentos e problemas de ordem ambiental, como poluição de mananciais hídricos (Giasson et al, 2002).…”
Section: Resultsunclassified
“…Therefore, a textural index may be inappropriate for CHa-1 since it is insensitive to clay mineralogy (Rogeri et al, 2016). Low-crystallinity iron and aluminum oxyhydroxides are some of the main components of the clay fraction responsible for P adsorption (Vilar et al, 2010;Gonçalves et al, 2011). Using P-rem instead of the clay content index reassigned 45% of the soils into different buffering classes.…”
Section: Range Of Interpretationmentioning
confidence: 99%
“…Therefore, these two soil types should have very different buffering capacities. Several studies showed the effect of mineralogy on the adsorption capacity of P (Bahia Filho et al, 1983;Vilar et al, 2010;Gonçalves et al, 2011). However, the current classification system (Manual…, 2004) assumes that soil types within the same clay class all have similar P buffering capacities despite the significant differences in their mineralogies.…”
Section: Introductionmentioning
confidence: 99%